(3EOGQI GdehGO (B:s (3GdTQGA hGdJNRjf ef efXhQ cej (B/s - (3Ybjdj, YeQ hUajs; (3GdehShj, efYe ReRjQs; (3GdYHOdj, bMWGf HOQ s ((3YeGf(B: s (3OGQ hGFd(B, s, 2009)
(3hXjaI GdTQGA(B: (3eGgjI hXjaI GdTQGA, JfXje hXjaI GdTQGA, GSJQGJjLjGJ GdTQGA, JMOjO GdMLe GdGbJUGOj dWdHjI GdTQGA, GNJjGQ eUOQ GdTQGA GdefGSH, GSJdGe haMU GdeTJQjGJ, GdTQGA HGdLhOI GdefGSHI, TQGA GdJLgjRGJ GdQCSeGdjI, HjY eNdaGJ GdGfJGL GdUfGYj, fXGe GdeYdheGJ hGdSLdGJ GdNGUI HhXjaI GdTQGA, Jbjje GOGA hXjaI GdTQGA, hXjaI GdJNRjf(B: (3eGgjI hXjaI GdJNRjf hCgejJgG, JfXje GdJNRjf, ehbY GdeNGRf OGNd GdefXeI hJUejegG hJfXjegG OGNdjG, JMOjO eSJhjGJ GdeNRhf, GLQGAGJ GdYed aj eLGd GdJNRjf, YedjI GdefGhdI aj GdeNGRf, GdQbGHI Ydi GdeNRhf, hXjaJG GdTQGA hGdJNRjf Yed eJcGed aj Xd fXGe GdGMJjGLGJ ef GdehGO GdUfGYjIs
(3HHdjhZQGajG(B: (3U(B.409s
Keywords: (3GOGQI GdeTJQjGJs; (3GdGfJGLs; (3GdJNRjfs; (3GdQbGHIs